Monoclonal antibodies to human growth hormone induce an allosteric conformational change in the antigen. - Mazza, M M (1989)
We re-investigated the properties of a monoclonal antibody (mAb), 4D11, to human growth hormone (hGH) that showed a very weak affinity, recognizing hGH only when the hormone was solubilized on a solid surface. MAb4D11 did not significantly bind 125I-hGH. It was found that three mAb directed to different hGH epitopes (mAb 3C11, 10C1 and NA71) were able to induce the binding of the soluble antigen to mAb 4D11. The co-operative effect could be demonstrated by the formation of binary complexes (Ag:Ab, 1:2) detected by high-performance liquid chromatography (HPLC) and by the increase of radioactivity found when the synergistic mAb were added to 125I-hGH incubated with mAb 4D11 immobilized on polyvinyl microplates. Other possible explanations, such as the formation of cyclic complexes or the generation of a new epitope in the Fc fragment of the first antibody (Ab), were dismissed because the Fab fragment of one of the enhancing mAb (3C11) gave the same effect as the intact Ab. The data suggest that the hGH molecule undergoes a localized conformational change after binding to mAb 3C11, NA71 or 10C1 and that mAb 4D11 binds with high affinity to the modified region of the hormone. The formation or not of ternary complexes (Ag:Ab, 1:3) was used to localize the 4D11 epitope on the surface of the Ag. It is suggested that mAb 4D11 recognizes a conformational change produced in the region defined by the AE5/AC8 epitopes, which is close to the hGH antigenic domain only expressed when the protein is immobilized on plastic surfaces.